Bacterial-Specific Aggregation and Killing of Immunomodulatory Host Defense Peptides - Nauman Nazeer; Juan Carlos Rodriguez-Lecompte; Marya Ahmed (MDPI AG, 2021)
This study involves the design and development of disulfide bridge-linked antimicrobial peptides using the host defense protein Angiogenin 4 (chAng4) as a template. The mini peptides derived from chAng4 (mCA4s) were evaluated for their antibacterial efficacies in various pathogenic bacterial strains, and the role of the oxidation state of thiols in the peptide sequence and its implication on antibacterial properties were explored. A remarkable property of these synthetic mCA4 peptides is their capability to flocculate bacteria and mediate bacterial-specific killing, in the absence of any other external stimulus. mCA4s were further evaluated for their cellular uptake, hemolytic activities, toxicities, and immunomodulatory activities in different eukaryotic cell lines. The results indicate that disulfide bridge-containing cationic amphipathic peptides show superior antibacterial efficacies, are nontoxic and nonhemolytic, and mediate bacterial flocculation and killing, in the absence of external stimuli.